When the media matters for electoral performance (Sociologisk Forskning, 2018)
In this article, we analyse the connection between media exposure and opinion polls for political parties or “the media influence”. We compare two parliamentary periods in Sweden: 2006–2010 and 2010–2014. Our results show that the media is important for the anti-immigration party, the Sweden Democrats (SD) in the first period. This is not the case, or at least less so, for the other parliamentary parties. In the second period, media exposure wanes in importance for explaining poll fluctuations as well as shifts from national to regional media for the Sweden Democrats. These findings are in consonance with previous research which underlines that the media´s influence on electoral performance differs before and after the party has crossed the electoral threshold to the national parliament.
Keywords: media; party politics; polling behaviour; life cycle